Meningkatkan Minat Belajar Siswa pada Pelajaran PAK dan BP Melalui Metode PBL dengan Media Canva di Kelas 8 SMP N 11 Ngabang - Andrianus Andrianus; Mawarni Gea; Agustinus Mulyono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to increase students' learning interest in the subject of Catholic Religious Education and Character Education through the implementation of Problem Based Learning (PBL) using Canva media in the 8th grade at SMP N 11 Ngabang. This study is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observation, questionnaires, interviews, and tests. The results showed that the implementation of PBL with Canva media was able to improve students' interest and engagement in learning, as well as enhance their understanding of the material. By the end of the second cycle, 80% of students showed increased learning interest, and 75% actively participated in learning activities. This improvement was also reflected in the evaluation results, where 80% of students demonstrated a good understanding of the material. Thus, PBL with Canva media can be an effective alternative to improve the quality of learning.